Exploring physical performance using basic fitness test among collegiate students - Samiha Mohamed Ibrahim Abd Elkader; Tarek Mohamed Fathi El-Gohary (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the effect of recreational status, body weight and risk factors on physical fitness of general students and on agility of physical therapy students. Method: The cross-sectional study was conducted at Taibah University, Medina, Kingdom of Saudi Arabia, from November 2018 to April 2019, and comprised general and physical therapy students from the College of Medical Rehabilitation Sciences. Data was obtained related to risk factors, like overweight, smoking and recreational status. Upper body strength, agility and endurance were measured using flexed-arm hang, 11x10 shuttle sprint test, and 1000-meter run test respectively. Data was analysed using SPSS 23. Results: Of the 50 subjects, 30(60%) were physical therapy students and 20(40%) were general students. Overall mean age of the sample was 21.54±1.83 years (range: 18-26), and mean body mass index was 23.34±3.37kg/m2 (range: 16.8-29.4kg/m2). The mean values for overweight status and number of risk factors were significantly different for the shuttle-sprint test (p<0.05), but were non-significant for the recreational status (p>0.05). All the assessed variables had non-significant association (p>0.05) in terms of flexed-arm hang test. Overall, 29(58%) subjects could not complete the 1000-meter run test, and 44(88%) found it a strong exertion. Conclusions: Unhealthy lifestyle significantly impaired physical fitness. Key Words: Agility, Endurance, Motor activity, Risk factors, Young adult.